Terror of History History of Terror: Exploring dialectic process visually - M. Adil (Law Text Culture, 2008)
The work Terror of History History of Terror (TOHHOT) is made of discs of bread, words, a cello bow and a wire coat-hanger. It is a visual unit that was part of a larger work in progress throughout 2006–2007. In the larger work I set out, amongst other things, to investigate and experiment with the visual properties of apparently everyday materials. I start with and depart from the assumption that such materials carry a relatively fixed range of associations, alone and in relation to one another, within the various contexts in which they are used or known of. This includes aspects of language, such as words and sentences. This work can be seen as a contribution towards generating provisional visual stimuli that might trigger interruptions to our habitual, usually unexamined, expectations of ‘meaning’. The provisionality extends to our language of everyday contact and exchange.